2018
DOI: 10.1159/000496200
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte Progenitor Cell Proliferation and Fate after White Matter Stroke in Juvenile and Adult Mice

Abstract: The incidence of stroke in children is 2.4 per 100,000 person-years and results in long-term motor and cognitive disability. In ischemic stroke, white matter (WM) is frequently injured, but is relatively understudied compared to grey matter injury. Previous research suggests that the cellular response to WM ischemic injury is different at different ages. Little is known about whether WM repair mechanisms differ in children and adults. We utilized a model of focal ischemic WM injury to determine the oligodendro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Moreover, the loss of BCAS1 specifically induced hypomyelination and expression of inflammation-related genes in the brain [20]. In line with previous studies, we found increased Bcas1 levels after stroke which are likely to represent a compensatory mechanism of oligodendrocyte proliferation after hypoxia and energy deficiency [27]. Bcas1 levels were increased in AGAT -/-mice and correlate with cognitive impairment [19].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the loss of BCAS1 specifically induced hypomyelination and expression of inflammation-related genes in the brain [20]. In line with previous studies, we found increased Bcas1 levels after stroke which are likely to represent a compensatory mechanism of oligodendrocyte proliferation after hypoxia and energy deficiency [27]. Bcas1 levels were increased in AGAT -/-mice and correlate with cognitive impairment [19].…”
Section: Discussionsupporting
confidence: 89%
“…The repairability of CNS in the peri-infract area after stroke is limited. Dingman et al [ 42 ] found that focal WM stroke mice had a profound increase in oligodendrocyte progenitor cells 24 h after ischemia, which was sustained for up to 7 days, but these new cells did not survive to maturity after WM stroke. To further determine the protective effect of EA on myelin fibers in ischemic WM, we employed immunohistochemistry and western blot methods to detect the expression of Nogo-A and NgR.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, stroke induces a strong proliferative response of OPCs, which migrate to the affected area and mature into myelinating oligodendrocytes ( Figure 3B ) ( Zhang et al, 2011 ; Bonfanti et al, 2017 ). This proliferative response seems to be age-dependent ( Dingman et al, 2018 ). However, the proportion of the newly formed oligodendrocytes that reach a mature stage after stroke is surprisingly low ( Bonfanti et al, 2017 ; Dingman et al, 2018 ).…”
Section: Oligodendrocytesmentioning
confidence: 99%
“…This proliferative response seems to be age-dependent ( Dingman et al, 2018 ). However, the proportion of the newly formed oligodendrocytes that reach a mature stage after stroke is surprisingly low ( Bonfanti et al, 2017 ; Dingman et al, 2018 ). The mechanisms of this developmental impairment are not yet clear, although excitotoxicity, inflammation, and oxidative stress seem to play a key role ( Figure 3B ).…”
Section: Oligodendrocytesmentioning
confidence: 99%